An anti-windup control strategy to actuator saturating input voltage for active magnetic bearing system. Issue 3 (3rd May 2016) - Pati, Avadh; Negi, Richa
Abstract : Purpose: – The active magnetic bearing (AMB) is highly non-linear and unstable system. In general most of physical systems, conventional PID control strategies are employed for their stable operation but the dynamics of the system are influenced by input voltage saturation that degrades the performance of the system. The conventional PID control scheme does not work properly alone. In such a situation, PID faces windup phenomenon that leads to instability in the system. To overcome this problem, an anti-windup control scheme leads to stable and smooth operation of AMB system. The paper aims to discuss these issues. Design/methodology/approach: – The proposed anti-windup control strategy is based on dynamic output feedback that is applied on linearized AMB system to stabilize and avoid the input voltage saturation effect in the actuator. Findings: – An anti-windup controller is designed for AMB system in presence of input voltage saturation. The stability of AMB system with anti-windup controller is derived in sense of Lyapunov and expressed as linear matrix inequality problem for AMB system and the designed anti-windup controller also enlarges the region of attraction of considered AMB system. Originality/value: – T-S fuzzy technique is used for obtaining local linear model of non-linear AMB system for easy and simple implementation of anti-windup control scheme. In proposed methodology the region of attraction for anti-windup compensator is also discussed. The effectiveness of proposed method is verified by the numerical simulation results for considered AMB system and domain of attraction or stability region of closed-loop AMB system are also calculated using eigenvalue optimization technique for both the cases such as with and without anti-windup controller. The comparative result and the contribution of proposed control strategy are also discussed.